Evaluation of locally produced microbial phytases and their by-products as additives in broiler nutrition - Khin, San Mu (2011)
Phosphorus (P) is a critical and expensive mineral in poultry nutrition. It is an essentially important mineral for the development of skeletal system and metabolism of broiler chickens. Two-thirds of P provided in typical broiler feed ingredients such as corn and soybean meal is bound to phytic acid. Phytic acid is of low availability to monogastric animals. such as poultry and pigs. due to the lack of phytate hydrolyzing enzyme, phytase. The addition of microbial phytase is an effective way to release a portion of phosphorus bound to the phytate in maize and soybean meal, thereby increasing improving P availability and reducing P excretion into the environment, Five experiments were conducted to evaluate the potential of locally produced microbial phytases as additive in broiler nutrition. In the first experiment. two locally produced microbial phytases (ASUIA279 and ASUIA271) were evaluated for their efficiency in improving growth performance. bone and serum mineralization. and phosphorus utilization of broiler chickens fed on corn and soybean meal based diet in a three-week study. The addition of 1000 units/kg feed of ASUIA279 phytase to the phosphorus deficient diet significantly increased (P< 0.05) body weight gain, tibia ash and phosphorus content, serum phosphorus concentration and phosphorus utilization at 21 days of age. The second experiment was conducted to evaluate the efficacy of ASUIA279 phytase at graded levels (500, 1000 and 1500 units/kg diet) on performances of broiler chickens fed corn soybean meal based diet in a 42-day study. Except for feed conversion ratio (FCR) and serum minerals (calcium and phosphorus), the improvement (P<0.05) in weight gain and feed intake. bone ash and bone P, and phosphorus retention were observed in the birds when phosphorus deficient diet was supplemented with phytase (1000 and 1500 units/kg feed) But the improvements were significantly (P<O.05) lower than the results observed with the adequate P diet. Five hundred units/kg feed of phytase supplementation improved only growth performance of broiler chicken in comparison with negative control diet. The third experiment was conducted to investigate the efficacy of phytase at graded dietary levels of non phytate phosphorus on performance of broiler chickens. Without considering interaction effect, both phytase supplementation and, dietary levels of non phytate phosphorus gave significant (P<().05) effects on all parameters (growth performance, bone and serum mineralization. nutrient utilization) except serum calcium level. Dietary levels of 0.251% non phytate phosphorus gave the lower performance (P<0.05) than dietary level of 0.33% and 0.45% non phytate phosphorus. Interaction between phytase and dietary levels of non phytate phosphorus showed that supplementation of phytase gave significant improvement (P<0.05) in body weight at dietary levels of 0.25 and 0.33% non phytate phosphorus, feed conversion ratio at dietary levels of 0.33% nPP and bone P content and P retention at dietary levels 0.25 and 0.33 % nPP. But dietary levels of 0.33% non phytate P with phytase supplementation gave better response than dietary levels of 0.25 (Yt) nPP and these results were comparable with the results obtained by the dietary levels of reference diet (nPP 0.45%). Supplementation of phytase at dietary levels of 0.45% nPP did not give additional positive response in all measurements. Experiment 4 was conducted to study the effects of centrifuged phytase and uncentrifuged phytase in rice bran media of ASUIA279 at 1000 units/kg feed on broiler chickens fed corn-soybean diet. Both centrifuged and uncentrifuged phytase supplementation gave significant improvement (P<O.05) in growth performance of broiler chickens (body weight gain and FCR) in comparison with negative control diet. The effect by centrifuged phytase supplementation was significantly (P<0.05) better than that of normal phosphorus adequate diet. However. bone mineralization, nutrient retention and excretion (P, Ca. and crude protein) were only significantly improved (P<0.05) by supplementation of centrifuged phytase. In experiment 5, the effects of fermented rice bran, a bio-converted byproduct of phytase production on performance of broiler chickens were evaluated in comparison with untreated rice bran. The contents of crude protein and crude fat were increased in the fermented rice bran and phytate P content was reduced as compared to untreated rice bran. Inclusion of 1(Jolt) untreated rice bran or fermented rice bran in corn soybean meal based diet did gave the same effects on performances of broiler chicken except for total P retention and can reduce feed cost. The addition of 10% fermented rice bran in the corn soybean meal diet produced better bone mineralization and P retention in comparison with untreated rice bran. These studies indicated that the locally produced microbial phytase. ASUIA279 has the potential to be used in commercial poultry operations. The fermented rice bran. byproduct of phytase production can be utilized as chicken feed without giving detrimental effects.